Analisis Kinerja dan Efisiensi Pengelolaan Dana Zakat: Studi Baznas Yogyakarta Periode 2015-2018 - S, Nurfadilah Maulana (LAA MAISYIR : Jurnal Ekonomi Islam, 2020)
This research to analyze the performance and efficiency of the institution BAZNAS Yogyakarta as a central institution coordinator gathering Zakat fund that must have a good and efficient performance. This research measures the performance of the Zakat agency through institutional indicators and the impact of the recipient of Zakat from the National Zakat Index (NZI), and measures the efficiency using the method Data Envelopment analysis (DEA). The sample used in this study is the audited financial annual report of 2015-2018. Based on the results of performance analysis, BAZNAS Yogyakarta has an index value of 0.433, which classifies the performance of the Zakat agency as "good enough ", the results of the efficiency analysis of 100% in the year 2015, 2017 and 2018, subsequently in 2016 only achieve efficiency of 97% and 3% that is inefficient. So the results of this research can be a reference for BAZNAS Yogyakarta further improve performance that is still less efficient and maintain the maximum performance to remain the center coordinator of the institution gathering Zakat fund that is entrusted by the Government and people of Yogyakarta.